A MOF adsorption material and mixed matrix membrane for efficient chromium removal

By developing a three-dimensional cationic frame MOF adsorbent material and a mixed matrix membrane, the ion exchange mechanism is used to remove chromium ions in water, solving the problems of poor chromium ion removal effect and high cost in the prior art, and achieving efficient and low-cost wastewater purification Effect.

CN118994627BActive Publication Date: 2025-01-14SHANTOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411467469.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The prior art has poor chromium ion removal effect in wastewater, high cost of adsorbent materials, and difficult to process and prepare into separation membranes, which affects practical application.

Method used

Develop a ternary hybrid MOF adsorbent material based on a three-dimensional cationic framework to exchange chromium ions in water through an ion exchange mechanism, and prepare a mixed matrix membrane with polyethyleneimine and polyvinylidene fluoride to achieve efficient removal of heavy metal chromium ion.

Benefits of technology

The material exhibits ultra-high adsorption capacity and fast mass transfer rate, can effectively remove chromium ions in aqueous solution, meets the standards of many countries and organizations, is easy to prepare, is low in cost, and has broad practical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994627B_ABST
    Figure CN118994627B_ABST
Patent Text Reader

Abstract

The present invention relates to a MOF adsorption material for efficient chromium removal and a mixed matrix membrane thereof. The general structural formula of the MOF adsorption material for efficient chromium removal is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, belongs to P ‑3 space group, with a one-dimensional hexagonal pore ternary hybrid three-dimensional cationic framework structure. The green macro-production of the material can be achieved by rapid stirring at room temperature, with low cost and easy processing. The MOF material of the present invention combines the advantages of PEI and PVDF to successfully prepare a mixed matrix membrane with excellent performance; dichromate pollutants in water can be quickly and efficiently removed by ion exchange, and chromium ion-contaminated water sources can be purified to meet the World Health Organization, the United States Environmental Protection Agency, and China's groundwater Class III standards; it has broad practical application prospects and market value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wastewater treatment, and in particular relates to a MOF adsorption material for efficient chromium removal and a mixed matrix membrane thereof. Background Art

[0002] Although water is the most abundant resource on earth, it is estimated that one quarter of the world's population lacks access to uncontaminated water. Removing trace pollutants (such as heavy metals) from water is one of the most pressing but technically difficult challenges in the global water treatment field. Among them, chromium ion pollution is one of the most serious pollution. Chromium is a metal element with redox properties. It usually exists in trivalent and hexavalent forms in aqueous solution. Compared with trivalent chromium ions, hexavalent chromium ions are more harmful and usually exist in the form of oxoacid anions in aqueous solution. It is reported that hexavalent chromium ions can corrode the digestive tract in the human body and cause symptoms such as vomiting, bloody stools, and dehydration; red blood cells in the human body can also cause obstruction of blood oxygen transport due to hexavalent chromium ions; at the same time, hexavalent chromium ions are also listed as one of the highly carcinogenic and teratogenic pollutants by the World Health Organization. Therefore, the removal of chromium ions in water has received widespread attention.

[0003] In order to achieve the selective removal of chromium in wastewater, the main methods include ion exchange, adsorption, membrane separation, electrocoagulation, and photocatalytic degradation. Among these methods, membrane separation technology has the advantages of simple process, low energy consumption, low cost, no secondary pollution, and good separation effect, and has been widely used in the field of water treatment. The ion exchange method has the advantages of high adsorption capacity, fast adsorption rate, and high removal efficiency. The separation membrane for chromium removal based on the ion exchange mechanism still has problems such as poor removal effect of adsorbent materials, high cost, and low removal efficiency after processing into membranes. Designing membrane materials that can efficiently remove chromium ions in wastewater is of great significance to solving the current problem of removing heavy metal ion pollutants from wastewater.

[0004] At present, many materials for removing chromium from aqueous solutions have been reported, such as activated carbon, metal oxides, organic polymers, zeolites, etc. However, these traditional adsorbent materials cannot achieve deep and efficient removal of chromium from aqueous solutions due to low adsorption capacity, poor separation selectivity, slow adsorption rate, etc. Moreover, traditional adsorbent materials are difficult to process into separation membranes, which affects practical applications. Therefore, the development of new chromium adsorption materials that are efficient, stable in nature, good in performance, and easy to process into separation membranes is the key to solving this problem. Summary of the invention

[0005] The present invention aims at the problems of poor removal effect of heavy metal chromium ion pollution in wastewater and high cost of adsorbent materials, and provides a ternary hybrid cationic MOF adsorbent material with SLN network structure and a preparation method of a mixed matrix membrane thereof, as well as application in removing chromium ions in aqueous solution. The material can quickly exchange with chromium ions in water based on the ion exchange mechanism and has an ultra-high adsorption capacity. The mixed matrix membrane constructed based on the material provides an effective solution for efficiently removing heavy metal chromium ions in wastewater.

[0006] A highly efficient MOF adsorbent for chromium removal is a ternary hybrid MOF material based on a three-dimensional cationic framework that removes chromium ions from water through an ion exchange mechanism. The ternary components include zinc ions, organic ligands TMeImB, and coordinated NO3 - , the counter anion of the cationic framework is NO3 - , the counter anion NO3 distributed on the pore surface - Cr2O7 can be achieved by anion exchange 2- The adsorption of 18 H 18 N6)3(NO3)](NO3)5, belongs to P -3 space group, a = b =22.2141(2) Å, c =11.37760(10)Å, α = β =90°, γ =120°. β -Si3N4 has the same network structure (sln), with characteristic hexagonal one-dimensional channels and good mass transfer rate; the asymmetric unit structure of this material is characterized by Zn (II) adopting a regular tetrahedral coordination mode, coordinated with three nitrogen atoms of organic ligand TMeImB and a bridging NO3 - Oxygen atom coordination. The material exhibits good solvent stability, water stability and acid-base stability.

[0007] Porous materials, especially metal-organic frameworks (MOFs), have the characteristics of large specific surface area and pore volume, high porosity, strong structural and functional designability, and have shown great application potential in the capture and removal of oxygen-containing anion pollutants in aqueous solutions. In particular, ionic MOFs have shown great potential for the capture and removal of Cr2O7 in water. 2- The removal of anionic pollutants showed obvious advantages.

[0008] The large particle preparation method of the above-mentioned MOF adsorption material with high efficiency in removing chromium comprises the following steps: dissolving the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene and zinc nitrate hexahydrate in a mass ratio of 1:1-1.2 in a mixed solvent of methanol and deionized water in a volume ratio of 3:1, carrying out a solvent thermal reaction, heating at a constant temperature of 120°C for 3-6 days, cooling to room temperature, filtering, washing and drying.

[0009] Furthermore, the mass ratio of the organic ligand to the metal salt is 1:1-1.2; more preferably, the mass ratio of the organic ligand to the metal salt is 1:1; and the solvents selected for washing include DMF, deionized water, and methanol.

[0010] The method for preparing the powder crystalline state of the above-mentioned MOF adsorption material with high efficiency of chromium removal in large quantities at room temperature comprises the following steps:

[0011] (1) Dissolve the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene in methanol solution at a concentration of 2 mg / mL in a volume of 150 mL;

[0012] (2) Dissolve zinc nitrate hexahydrate in deionized water at a concentration of 6 mg / mL in a volume of 50 mL;

[0013] (3) under magnetic stirring, adding dropwise the aqueous solution of zinc nitrate hexahydrate obtained in step (2) to the solution of organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzyl alcohol obtained in step (1);

[0014] (4) After the addition is complete, stop stirring and let stand at room temperature for 3-12 hours to obtain an emulsion that does not settle. Centrifuge, filter, wash repeatedly with methanol and deionized water, and dry in vacuum.

[0015] Furthermore, in step (3), the mass ratio of zinc nitrate hexahydrate to the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene is 1:1-1.5. Preferably, the concentration of the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzyl alcohol solution is 2 mg / mL, and the added volume is 150 mL; the concentration of the zinc nitrate hexahydrate solution is 6 mg / mL, and the added volume is 50 mL.

[0016] Furthermore, the concentration of the methanol solution of the organic ligand is 2 mg / mL; the concentration of the aqueous solution of Zn(NO3)2·6H2O is 6 mg / mL; and the mass ratio of the organic ligand to the metal salt is 1:1.

[0017] Furthermore, the standing time at room temperature is preferably 12 hours.

[0018] Furthermore, the washing solvent is methanol and deionized water, and the washing times are three times; the vacuum drying temperature is 90-110°C, and the preferred temperature is 100°C.

[0019] A mixed matrix membrane comprising the above-mentioned MOF adsorption material for efficient chromium removal.

[0020] Furthermore, the above-mentioned MOF adsorption material with high efficiency in removing chromium, polyethyleneimine (PEI) and polyvinylidene fluoride (PVDF) are mixed.

[0021] The method for preparing the mixed matrix membrane comprises the following steps:

[0022] (S1) dispersing the MOF adsorption material with high efficiency in removing chromium in N,N-dimethylformamide to form a uniform solution;

[0023] (S2) adding polyethylene glycol and polyvinylidene fluoride, stirring at a constant temperature of 70° C. for 12-24 hours, and standing and degassing for 12-24 hours to obtain a membrane-building solution;

[0024] (S3) applying the membrane-building solution obtained in step (S2) on a smooth glass plate using a scraper with a thickness of 200 μm, then immersing the glass plate in deionized water, taking it out, and drying it to obtain a MAF-stu-2-PVDF mixed matrix membrane;

[0025] (S4) The MAF-stu-2-PVDF mixed matrix membrane obtained in step (S3) is completely immersed in the aqueous solution of PEI, and the aqueous solution of epichlorohydrin is added dropwise to the aqueous solution of polyethyleneimine. After the addition is completed, the mixed solution containing MAF-stu-2-PVDF is sealed and allowed to stand at a constant temperature of 60°C for 6-12 hours, and finally dried and taken out for use.

[0026] Furthermore, the mass ratio of MOF adsorption material for efficient chromium removal, polyvinylidene fluoride, N,N-dimethylformamide, and polyethylene glycol added is 11.2:16:74:10; the concentration of polyethyleneimine is 5 g / L, and the concentration of epichlorohydrin is 6 mL / L.

[0027] Furthermore, the molecular weight of the polyethylene glycol is 400; the molecular weight of the polyvinylidene fluoride is 500,000.

[0028] Furthermore, the reaction standing time of the mixed solution of MAF-stu-2-PVDF and PEI aqueous solution is preferably 12 hours.

[0029] The above-mentioned MOF adsorption material with high efficiency in chromium removal is used to remove dichromate ions from wastewater.

[0030] The above mixed matrix membrane is used for removing dichromate ions from wastewater.

[0031] The novel ternary hybrid cationic framework material MAF-stu-2 and the mixed base MAF-stu-2-PEI-PVDF of the present invention show excellent chromium ion removal ability in aqueous solution.

[0032] (1) MAF-stu-2 crystalline material can achieve an ultra-high chromium adsorption capacity of 352 mg / g in a 1000 ppm dichromate aqueous solution.

[0033] (2) MAF-stu-2 crystalline material meets the U.S. Environmental Protection Agency's chromium removal standards and can reduce the dichromate aqueous solution from 500 ppb to less than 100 ppb (19 ppb).

[0034] (3) MAF-stu-2 crystalline material meets the World Health Organization's chromium removal standards and can reduce the dichromate aqueous solution from 200 ppb to less than 50 ppb (28 ppb).

[0035] (4) MAF-stu-2 crystalline material complies with the groundwater quality standards of the People's Republic of China and can reduce the chromium ion concentration that is not suitable for drinking water to a concentration standard suitable for centralized drinking water sources and industrial and agricultural water use (groundwater Class III standard: concentration less than 50 ppb).

[0036] (5) The flux of pure water of the MAF-stu-2-PEI-PVDF mixed matrix membrane is 201.2LMH under a pressure of 2 bar; under the same pressure, the retention rate of the mixed matrix membrane for a 10 ppm aqueous solution of dichromate exceeds 99.5%.

[0037] Compared with the prior art, the MOF adsorbent material of the present invention has a stable structure, is easy to prepare, can be prepared in large quantities at room temperature, is low in cost, and is easy to process. The MOF material of the present invention combines the advantages of PEI and PVDF to successfully prepare a mixed matrix membrane with excellent performance; it can quickly and efficiently remove dichromate pollutants in water through ion exchange, and can purify water sources contaminated by chromium ions to meet the standards of the World Health Organization, the United States Environmental Protection Agency, and China's groundwater Class III; it has broad practical application prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of the structure of the MAF-stu-2 material of Example 1.

[0039] Figure 2 The powder X-ray diffraction patterns of MAF-stu-2 in Example 1 in different solvents.

[0040] Figure 3 The figure is the powder X-ray diffraction pattern of MAF-stu-2 in Example 1 at different pH values ​​in aqueous solution.

[0041] Figure 4 This is a photograph of the large-scale preparation of MAF-stu-2 at room temperature in Example 2.

[0042] Figure 5 This is a scanning electron microscope image of MAF-stu-2 in Example 2.

[0043] Figure 6 This is the powder X-ray diffraction pattern of MAF-stu-2 prepared in large quantities at room temperature in Example 2.

[0044] Figure 7 This is the powder X-ray diffraction pattern of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 3.

[0045] Figure 8 This is the infrared spectrum of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 3.

[0046] Fig. 9 This is the thermogravimetric analysis spectrum of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 3.

[0047] Fig.10 This is the pure water contact angle test of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 3.

[0048] Fig.11 This is a scanning electron microscope image of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 3.

[0049] Fig.12 This is the pure water flux spectrum of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 4.

[0050] Fig.13 This is the dichromate rejection rate spectrum of the MAF-stu-2-PEI-PVDF mixed matrix membrane in Example 4. DETAILED DESCRIPTION

[0051] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0052] Example 1

[0053] Synthesis of MAF-stu-2 Large Crystal Materials

[0054] 4 mg of organic ligand TMeImB and 4 mg of zinc nitrate hexahydrate were dissolved in a mixed solvent containing 3 mL of methanol and 1 mL of deionized water, and reacted at 120 °C for 3 days. After the reaction, it was slowly cooled to room temperature in the air. After repeated washing with methanol and deionized water, filtration and drying, a relatively pure ternary hybrid cationic framework MOF material (yield of about 83%, based on organic ligands) was obtained, named MAF-stu-2.

[0055] In order to test the solvent stability of MAF-stu-2, the synthesized fresh samples were immersed in common organic solvents for 3 days and then the PXRD data of the samples were measured ( Figure 2 ), it can be seen from the figure that this series of materials still maintains good structural integrity, indicating that they have good solvent stability.

[0056] In order to test the acid-base stability of MAF-stu-2, the synthesized fresh samples were immersed in aqueous solutions with pH = 2-13 for 3 days, and then the PXRD data of the samples were measured ( Figure 3 ), it can be seen from the figure that this series of materials still maintains good structural integrity, indicating that it has good acid-base stability.

[0057] In order to test the chromium ion removal ability of MAF-stu-2, the synthesized fresh sample was immersed in a trace amount of chromium ion aqueous solution for one day, and the chromium ion concentration in the filtrate was tested by ICP. The results in Table 1 show that the material exhibits excellent chromium removal ability and meets the World Health Organization, the United States Environmental Protection Agency, and China's groundwater Class III standards.

[0058] Table 1 Chromium ion removal capacity of MAF-stu-2 (World Health Organization, U.S. Environmental Protection Agency)

[0059]

[0060] Example 2

[0061] Synthesis of MAF-stu-2 Powder Crystalline Material

[0062] 300 mg TMeImB was dissolved in 150 mL methanol solution, 300 mg Zn(NO3)2·6H2O was dissolved in 50 mL deionized water, and the aqueous solution of Zn(NO3)2·6H2O was added drop by drop to the methanol solution of TMeImB under magnetic stirring. After the addition was completed, stirring was stopped and the mixture was allowed to stand at room temperature for 3-12 hours to obtain a non-precipitating white emulsion. The mixture was centrifugally filtered, washed repeatedly with methanol and deionized water three times, and dried under vacuum at 100 °C for one day to obtain a large amount of MAF-stu-2 powder crystalline material (yield of about 92%, based on organic ligand).

[0063] In order to characterize the MAF-stu-2 powder crystalline material prepared in large quantities at room temperature, Figure 4 and Figure 5 The pictures and scanning electron microscope photos of the white emulsion of MAF-stu-2 powder crystals are shown. The PXRD data of the sample were measured after filtration, washing and drying ( Figure 6 ), it can be seen that the material rapidly synthesized in large quantities under room temperature conditions is completely consistent with the simulated spectrum, and has better crystallinity than the material synthesized by the solvothermal method in Example 1.

[0064] Example 3

[0065] Synthesis of MAF-stu-2-PEI-PVDF mixed matrix membrane

[0066] (1) Take a certain amount of the MAF-stu-2 powder crystalline material prepared in Example 2 and disperse it in a certain amount of DMF by ultrasonic dispersion. After it forms a uniform solution, add a certain amount of PEG and PVDF. Stir the mixed solution at 70 °C for one day and let it stand for 12 hours to degas to obtain a membrane-building solution. Finally, apply the membrane-building solution on a smooth glass plate with a scraper with a thickness of 200 μm. After waiting for 30 seconds, place the glass plate in deionized water, soak it for one day, take it out and dry it for use, and obtain a MAF-stu-2-PVDF mixed matrix membrane.

[0067] (2) Completely immerse the MAF-stu-2-PVDF mixed matrix membrane in the PEI aqueous solution, and drop a certain amount of epichlorohydrin aqueous solution into the PEI aqueous solution. After the addition is completed, seal the mixed solution containing MAF-stu-2-PVDF and let it stand at a constant temperature of 60 °C for 6-12 hours. Finally, dry it and take it out for use.

[0068] In this embodiment, the mass ratio of MAF-stu-2 powder crystalline material, PVDF, DMF, and PEG is 11.2:16:74:10, the concentration of PEI is 5 g / L, and the concentration of epichlorohydrin is 6 mL / L.

[0069] To characterize the MAF-stu-2-PEI-PVDF mixed matrix membrane, Figure 7 PXRD data of MAF-stu-2-PEI-PVDF mixed matrix membrane. Figure 8 The infrared spectrum data of MAF-stu-2-PEI-PVDF mixed matrix membrane are shown in Figure 2. Figure 7 and Figure 8 It can be seen that the MAF-stu-2-PEI-PVDF mixed matrix membrane was successfully prepared. Fig. 9The thermogravimetric analysis results of MAF-stu-2-PEI-PVDF mixed matrix membrane show that the decomposition temperature is 220 ℃. Fig.10 This is the pure water contact angle diagram of the MAF-stu-2-PEI-PVDF mixed matrix membrane. The contact angle is 62°, indicating that the MAF-stu-2-PEI-PVDF mixed matrix membrane material has good hydrophilic properties and can increase the performance of the membrane material in achieving adsorption and separation in water. Fig.11 This is a scanning electron micrograph of the MAF-stu-2-PEI-PVDF mixed matrix membrane.

[0070] Example 4

[0071] Study on the performance of MAF-stu-2 and MAF-stu-2-PEI-PVDF mixed matrix membranes in removing dichromate ions from water

[0072] (1) MAF-stu-2 powder crystalline material was placed in a 1000 ppm dichromate aqueous solution and kept at 30 °C and 300 rpm in a shaker for one day. The atomic emission spectroscopy (ICP) test of the filtrate showed that the material had a strong affinity for Cr2O7 2- The adsorption capacity reached 352 mg / g, which is the highest value among MOF materials.

[0073] (2) The pure water flux of the MAF-stu-2-PEI-PVDF mixed matrix membrane under different osmotic pressures was tested by ultrafiltration cup. The pure water flux of the membrane material was 201.2 LMH at a pressure of 2 bar (e.g. Fig.12 ).

[0074] (3) The retention efficiency of the MAF-stu-2-PEI-PVDF mixed matrix membrane for a 10 ppm aqueous solution of dichromate at 2 bar pressure was determined by a cross-flow filtration device. The retention rate of the membrane material exceeded 99.5% (e.g. Fig.13 ).

[0075] Comparative Example 1

[0076] The mixed solvent containing 3 mL of methanol and 1 mL of deionized water in Example 1 was changed to a mixed solvent containing 2 mL of methanol and 2 mL of deionized water, and the other steps and conditions remained unchanged. Ultimately, the target product MAF-stu-2 large crystal material could not be obtained.

[0077] Comparative Example 2

[0078] The solvent thermal reaction temperature of Example 1 was changed to 115°C or 125°C, that is, the reaction at 120°C for 3 days was changed to the reaction at 125°C for 3 days or the reaction at 115°C for 3 days, and the yield of the product was greatly reduced. If the solvent thermal reaction temperature is lower than 115°C or higher than 125°C, the target product cannot be obtained.

[0079] Comparative Example 3

[0080] The scraper with a thickness of 200 μm in Example 3 was replaced with scrapers of other thicknesses (50, 100, 250, 400), and it was found that 200 μm was a good balance between interception effect and flux.

Claims

1. A MOF adsorption material for efficient chromium removal, characterized in that: The general structural formula is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, belongs to P -3 space group, a = b =22.2141(2) Å, c =11.37760(10)Å, α = β =90°, γ =120°, where C 18 H 18 N6 is 1,3,5-tri(2-methyl-1H-imidazolyl)phenyl; the MOF adsorption material with high efficiency in removing chromium has β -Si3N4 has the same network structure, Zn (II) adopts a regular tetrahedral coordination mode, with three C 18 H 18 The nitrogen atom of N6 is coordinated with a bridged NO3 - Oxygen atom coordination.

2. The method for preparing large particles of MOF adsorption material for efficient chromium removal according to claim 1, characterized in that: The method comprises the following steps: dissolving zinc nitrate hexahydrate and an organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene in a mixed solvent of methanol and deionized water in a volume ratio of 3:1 at a mass ratio of 1:1-1.2, carrying out a solvent thermal reaction, heating at a constant temperature of 120°C for 3-6 days, cooling to room temperature, filtering, washing and drying.

3. A method for preparing a large amount of powder crystalline MOF adsorption material for efficient chromium removal according to claim 1 at room temperature, characterized in that: The following steps are involved: (1) dissolving the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene in a methanol solution; (2) Dissolve zinc nitrate hexahydrate in deionized water; (3) under magnetic stirring, the aqueous solution of zinc nitrate hexahydrate obtained in step (2) is added dropwise into the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzyl alcohol solution obtained in step (1) at a mass ratio of zinc nitrate hexahydrate to organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene of 1:1-1.5; (4) After the addition is complete, stop stirring and let stand at room temperature for 3-12 hours to obtain an emulsion that does not settle. Centrifuge, filter, wash repeatedly with methanol and deionized water, and dry in vacuum.

4. A mixed matrix membrane comprising the MOF adsorption material for efficient chromium removal according to claim 1.

5. The mixed matrix membrane according to claim 4, characterized in that: The invention is prepared by mixing the MOF adsorption material for efficient chromium removal as claimed in claim 1, polyethyleneimine and polyvinylidene fluoride.

6. The method for preparing a mixed matrix membrane according to claim 5, characterized in that: The following steps are involved: (S1) dispersing the MOF adsorption material with high efficiency in removing chromium in N,N-dimethylformamide to form a uniform solution; (S2) adding polyethylene glycol and polyvinylidene fluoride, stirring at a constant temperature of 70° C. for 12-24 hours, and standing and degassing for 12-24 hours to obtain a membrane-building solution; (S3) applying the membrane-building solution obtained in step (S2) on a smooth glass plate using a scraper with a thickness of 200 μm, then immersing the glass plate in deionized water, taking it out, and drying it to obtain a MAF-stu-2-PVDF mixed matrix membrane; (S4) The MAF-stu-2-PVDF mixed matrix membrane obtained in step (S3) is completely immersed in the aqueous solution of PEI, and the aqueous solution of epichlorohydrin is added dropwise to the aqueous solution of polyethyleneimine. After the addition is completed, the mixed solution containing MAF-stu-2-PVDF is sealed and allowed to stand at a constant temperature of 60°C for 6-12 hours, and finally dried and taken out for use.

7. The preparation method according to claim 6, characterized in that: The mass ratio of MOF adsorption material for efficient chromium removal, polyvinylidene fluoride, N,N-dimethylformamide, and polyethylene glycol added is 11.2:16:74:10; the concentration of polyethyleneimine is 5 g / L, and the concentration of epichlorohydrin is 6 mL / L.

8. The use of the MOF adsorption material for efficient chromium removal according to claim 1, characterized in that: Used to remove dichromate ions from wastewater.

9. The use of the mixed matrix membrane according to claim 4, characterized in that: Used to remove dichromate ions from wastewater.

Citation Information

Patent Citations

  • MOF (metal-organic framework) separating layer film and preparation method thereof

    CN107398186A

  • Ternary imidazole ligand zinc complex and preparation method thereof

    CN110330516A